Rapid manufacturing of silica glass parts with complex structures through stereolithography and pressureless spark plasma sintering. Issue 1 (1st January 2022) - Cai, Peng; Guo, Liang; Liu, Liangzhi; Zhang, Qingmao; Li, Jiaming; Lue, Qitao
Abstract: This paper reports a method for preparing silica glass by pressureless spark plasma sintering (PL-SPS), which can rapidly manufacture silica glass parts with complex structures by coupling with stereolithography 3D printing technology. The rapid sintering process and microstructure evolution of silica glass prepared by PL-SPS were mainly investigated. The experimental results showed that the sintering temperature and dwelling time were the main factors affecting the PL-SPS of silica glass. The microstructure evolution indicated that the densification rate of the sample was very fast from 1250 °C to 1300 °C, and the interlayer defects caused by the printed layer thickness could be healed in the final stage of densification. Like conventional pressureless sintering, silica glass with a relative density of more than 99% and a visible-light transmittance of more than 90% could also be obtained through PL-SPS, but the entire working time was shortened from 22.53 h to 0.49 h.